Social Perception of Hard Coal Mining in Perspective of Region’s Sustainable Development - Bijańska Jolanta; Kuzior Aleksandra; Wodarski Krzysztof (Management Systems in Production Engineering, 2018)
This article presents a pilot study on the local community’s social perception regarding coal mines in Upper Silesia. The research was performed in connection with the smog, which was persistent and harmful to residents during the winter months of 2016. The researchers put forward to the local community the following two survey questions: 1. Is the image of coal mines in the eyes of the local community positive or negative? 2. Are coal mines socially responsible and is coal a good energy source? The aim of this article is to indicate the relationship of the local community to the presence of hard coal mines in the neighbourhood and their social role. Also, this work looks to identify the nuisances perceived by the inhabitants of the examined region about mining enterprises and whether these burdens should result in abandonment of hard coal mining. Pilot studies were conducted with the use of a diagnostic survey. The study was carried out in January 2017 on a sample of 267 people, comprising Silesian University of Technology students residing in Upper Silesia. An environmental survey technique was used. The researchers hypothesise that the image of mining and coal as a fuel for the local community is negative and the mines are not socially responsible enterprises. This research shows that the operation of mines is essential for society and its stability as it affects economic, social and energy safety. A large proportion of the respondents defined the image of mining as positive (108 people), but 76 people indicated that the image was rather negative. Most respondents pointed to the benefits of the mine’s operation. Opinions on social responsibility were divided, and most respondents failed to provide concrete examples of social engagement, so the first hypothesis was partly confirmed. Although the respondents pointed to various nuisances resulting from the mining companies operating in their environment, they also recognised significant social aspects related to employability and access to relatively cheap fuel. However, they do not realise the social involvement of mines, which is one of the conditions of sustainable development. Pilot studies allowed for the initial identification of problems and verification of the research tool utilised in this study.